Prevalence of elevated alanine aminotransferase (ALT) in pregnancy: A cross-sectional labor and delivery-based assessment. Issue 40 (7th October 2022) - Kushner, Tatyana; Park, Claire; Masand, Dana; Rosenbluth, Emma; Carroll, Carin; Grace, Marie; Rodriguez-Rivas, Clara; De La Cruz, Hernis; Overbey, Jessica; Sperling, Rhoda
Abstract : Since liver tests are not routinely checked in pregnancy, the prevalence of abnormal liver tests and liver-related abnormalities in pregnancy in a US-based population is not known. We sought to determine the prevalence of abnormal alanine aminotransferase (ALT) among pregnant Individuals who present to labor and delivery for evaluation and to evaluate prevalence of underlying diagnosed liver conditions. Prospective study evaluating liver tests in consecutive samples obtained on the labor and delivery unit. Patient characteristics were compared between those with and without abnormal ALT and those with and without abnormal ALT without a liver-related diagnosis made in clinical practice, using t tests for continuous measures and χ2 or Fisher's exact tests as appropriate for categorical measures. Logistic regression was utilized to identify factors associated with abnormal ALT in this subcohort to determine predictors of abnormal ALT in those without a known liver-related diagnosis. We collected 1024 laboratory specimens from 996 patients. Of these patients, 131 of 996 (13.2%) had elevated ALT ≥25 IU/L; 20 (2%) had ALT ≥50, 6 (0.6%) had ALT ≥125 and 3 (0.3%) had ALT ≥250. 61/131 (46.6%) of patients with ALT ≥25 IU/L had not had LTs checked during routine pregnancy care. 20 (15%) of individuals with abnormal LT had preeclampsia; 5 (4%) had cholestasis of pregnancy; 1 (0.8%) had hepatitis C; there were no other chronic liver diseases diagnosed. There were no significant demographic or clinical differences between those with and without ALT ≥25, whether liver disease diagnosis was made or not. We identified an over 10% prevalence of abnormal LTs in consecutive pregnant individuals who presented to L&D, most of whom did not have a liver-related condition diagnosed in clinical practice. Among those with liver-related diagnoses, PE and ICP were the most common among individuals with ALT≥25 IU/mL, with chronic liver disease rarely diagnosed. Further evaluation of the role of ALT testing as part of routine prenatal care is needed, particularly in establishing a baseline prevalence of liver test abnormalities in pregnancy and independent association with pregnancy outcomes.